University Tutoring and ICT: The Experience of a Teaching Innovation in Higher Education - González Lorente, Cristina; Martínez-Clares, Pilar; Pérez-Cusó, Javier; González-Morga, Natalia (Revista Complutense de Educación, 2023)
The use of information and communication technologies (ICT) in higher education has become widespread in recent years, while its application in everyday life is already ubiquitous. However, the use of ICT in career guidance and tutoring in the universities is scarce. This research aims to evaluate a teaching innovation that enhances university tutoring with the use of two technological tools: Kahoot and virtual forums. Through a quantitative research methodology, 238 students from the Faculty of Education at the University of Murcia participated by filling out an ad hoc designed satisfaction scale. The high Cronbach's Alpha denote an adequate scale for the data intended to be measured. Other results also show a high student satisfaction with Kahoot and tutoring identified by the professor through the help of digital tools, as is also highlighted in other studies on Kahoot (Reynolds et al., 2021) and university tutoring (Castillo y Aguilar, 2021). The lower satisfaction with the development of virtual forums invites further analysis, in education 4.0, from a qualitative perspective (Ajjawi y Boud, 2018) in future lines of research.
Keywords: university tutoring; virtual forums; teaching innovation; higher education; educational software